Teacher Performance: Factors InfluencingTeacher Performance - Bumay, Anitia Fadhila; Hariri, Hasan; Rini , Riswanti (International Journal of Educational Management and Innovation, 2023)
Teacher performance is a key to the success of a learning that takes place at schools. The better the teacher’s performance, the more educational goals will be achieved. Teacher performance in schools is influenced by certain factors. This article aims to investigate the factors that can affect the performance of a teacher in schools. This research used the literature review method where data collection was carried out through a collection of articles from 2018 to 2023. There are 10 international articles as references from Google Scholar. This article can be useful from a theoretical aspect, namely to increase knowledge about what factors can affect teacher performance, then practically it can be used as a reference for the next research. Keywords: Influence, Teacher Performance, School, Factor